Pengembangan Wisata Religi Makam Gus Dur di Kabupaten Jombang Pendekatan: Community Based Tourism: Religious Tourism Development of Gus Dur Sanctuary in Jombang Regency: Community Based Tourism Approach - Septa Mega Hera Kartika; Herman Cahyo Diartho; Fajar Wahyu Prianto (Journal of Regional and Rural Development Planning (Jurnal Perencanaan Pembangunan Wilayah dan Perdesaan), 2020)
Religious Tourism Development of Gus Dur Sanctuary in Jombang Regency: Community Based Tourism Approach Community based tourism is the concept of tourism development by involving the people or community in its activities and management. This study aims to determine priority factors that may affect community based tourism and development strategy of Gus Dur sanctuary religious tourism in Jombang Regency. The analytical method used in this case is Analytical Hierarchy Process (AHP) and Strengths, Weaknesses, Opportunities, Threats (SWOT) analysis. Based on the results of AHP analysis, it was found that the activity of the organization or society groups (0.382), increased cooperation government and society (0.269), the addition of facilities and infrastructure (0.182), and manufacture of regulation (0.167), factor activity of organizations/communities are considered most important in determining the priority development of religious tourism of Gus Dur sanctuary. The results SWOT analysis obtained, six development strategies, namely to involve the local community in tourism development and empowerment activities, to facilitate the development of business/industry through microcredits that can support people’s economy, to optimize the role of the government to increase the planned development targets, to facilitate development of home business/industry through courses and training institutions, improve cooperation with private sector to support tourism development, and improve cooperation between community and government or private sector in developing local economy.